MATHEMATICAL MODELLING OF CLINKER PRODUCTION WITH SERIAL FLOW PREHEATER CYCLONES AND PRECALCINER - Ahmet KOLİP (Civil Engineering Journal, 2019)
A simple mathematical model is presented for clinker production via a pyroprocessing unit consisting of serial flow preheater cyclone stages, a precalciner, a rotary kiln and a clinker cooler. The model equations are based on steady state material and energy balances for solid and gas phases around each piece of equipment. The contribution of fuel ash to rawmeal, recarbonation reactions in the preheater section and temperature dependence of specific heats are included in this model. A computer program has been developed to solve the model equations via an iterative procedure, yielding raw meal, stack gas, stack dust and temperature profiles and specific fuel consumption for a given set of input variables, thus enabling the user to investigate the impact of any design or process variable on the system performance. In this study the effects of fuel type and number of preheater stages on specific fuel consumption are investigated. The results indicate that in certain cases, by changing the fuel type, and by adjusting the degree of calcination in the precalciner when there is a fuel mix, energy savings equivalent to addition of extra preheater stage may be possible.